Unpacking zhi (zhi) in the Laozi: A semantic and epistemological analysis with focus on Western sinological perspectives - Guan, Yinlin (Asian philosophy, 2026)
This paper investigates the semantic range of the term zhi (zhi, to know) in the Laozi, providing the understanding of its epistemological implications. It argues that, contrary to the conventional belief that the Laozi dismisses knowledge, the Laozi endorses certain sorts of knowledge as guidance for action. Through a systematic analysis of zhi zhi in its various grammatical and syntactic contexts, the paper identifies three epistemological types: know-that knowledge (propositional awareness), know-how knowledge (practical skills), and knowing by acquaintance (familiarity). These distinctions illuminate the Laozi’ s complex attitude toward knowledge, which simultaneously critiques knowledge that fosters desires and distinctions and endorses a reflective understanding of one’ s cognitive limitations.